Anthropometric Assessment of the Nutrition III Female Children of Thar Desert - Singh, Madhu B (Annals of Arid Zone, 2016)
A study was conducted in 18 villages in three ecological regions i.e., Marusthali, Shekhawati and Luni Basin in Thar Desert. Data on six anthropometric measurements, along with demography and socio-economic aspects were collected for 1132 female children which revealed that 94.6% mothers and 48.8% fathers of female children were illiterate. Main occupation of 58.4% parents was agriculture. Body weight ranged from 14.4 kg (5 years) to 45.2 kg (17 year) and height ranged from 102.5 cm (5 year) to 156 cm (17 year) in girls. Height and weight of female children in Thar Desert are very low in comparison to National Center for Health Statistics (NCHS) (P <0.01). These results will help in planning and